Normal isomerization catalyst as well as preparation method and application thereof
By using SO42-/ZrO2, all-silicon molecular sieve and alumina active matrix in light alkane normal isomerization catalysts and loading precious metal components, the problems of insufficient catalyst activity and poor stability are solved, and high-efficiency light hydrocarbons are achieved Norm isomerization reaction and good selectivity.
Patent Information
- Application Number
- CN202311049097.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-18
AI Technical Summary
The existing light alkane isomerization catalysts have insufficient activity and poor stability, making it difficult to take into account both the high conversion rate and the selectivity of the target product.
An active matrix including acidic active component SO42-/ZrO2, a full silicon molecular sieve with an MFI structure and alumina is used, and the noble metal components are supported to adjust the central density of strong acid in the catalyst, and synergistically improve the activity and selectivity of the catalyst.
An efficient light hydrocarbon isomerization reaction is achieved, with high conversion and selectivity, and the stability of the catalyst is significantly improved.
Smart Images

Figure CN119488937A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a normal isomerization catalyst and a preparation method and application thereof. Background Art
[0002] Normal isomerization of light alkanes mainly includes C5 / C6 isomerization, n-butane isomerization and isobutane normalization. Among them, C5 / C6 isomerization is used to produce C5 / C6 isomerized oil, which basically does not contain sulfur, olefins and aromatics, and is an important clean gasoline blending component. N-butane isomerization can convert n-butane into isobutane, providing isobutane raw materials for butane-butene alkylation, isobutane-propylene co-oxidation (PO / MTBE), C3 / iC4 alkane dehydrogenation, isobutane dehydrogenation and other processes. Isobutane normalization can convert isobutane into n-butane, providing n-butane raw materials for processes such as steam cracking to produce ethylene and butane oxidation to produce maleic anhydride. Therefore, normal isomerization of light alkanes is an important supporting technology for upgrading the quality of oil products, an important means to expand the source of raw materials for ethylene units, and a key unit technology for n-butane oxidation to produce maleic anhydride, C3 / C4 alkane dehydrogenation, isobutane dehydrogenation, PO / MTBE and other processes. Efficient catalysts for the normal isomerization of light alkanes are the core of normal isomerization technology. There are two types of traditional catalysts for the normal isomerization of light alkanes, one is Pt-containing chloride alumina (Pt / Al2O3-Cl) catalysts, and the other is Pt or Pd-loaded zeolite molecular sieve (Pt(Pd) / zeolite) catalysts. Pt / Al2O3-Cl catalysts have the advantages of low reaction temperature and high single-pass conversion rate, but the disadvantage is that the catalyst is sensitive to raw material impurities, and the raw materials need to be strictly refined to remove impurities such as sulfur and water. During the isomerization reaction, chlorine needs to be continuously injected to maintain the catalyst activity, and the catalyst cannot be regenerated, which further limits the application of this type of technology. Pt(Pd) / zeolite catalysts have relatively loose requirements on impurities in the raw materials, but have low isomerization activity and selectivity.
[0003] Solid superacid catalyst is a new type of catalyst developed in recent years. In the prior art, it has been reported that inorganic acid-promoted zirconium-based solid superacid catalysts are used in light hydrocarbon isomerization reactions. CN107051420A discloses a n-butane isomerization catalyst and a preparation method thereof. The catalyst uses nano-scale tetragonal zirconium oxide as a carrier and is loaded with sulfate, molybdate and precious metals. When the catalyst is used for n-butane isomerization reaction, the reaction temperature is 220°C, 2.0 MPa, and the feed mass space velocity is 2.0 h -1, hydrogen / hydrocarbon molecular ratio of 1.2, the isomerization rate of n-butane is up to 39.7%. CN1164509A discloses a molecular sieve type superacid and its preparation method, wherein the catalyst is a hydrogen-type ZSM-5, ZSM-11 or β molecular sieve containing Ti or Zr metal elements. When the catalyst is used for the isomerization reaction of n-butane, at 100°C, normal pressure, and the n-butane gas space velocity is 800h -1 Under the condition of , the conversion rate of n-butane is 35% and the selectivity of isobutane is 78%. CN101745407A discloses a solid superacid catalyst and its preparation method. The catalyst converts zirconium hydroxide into a catalyst containing SO4 2- The solid catalyst is impregnated with a solution of , dried and mixed with silica sol, extruded and calcined, and then impregnated with a group VIII metal. The solid catalyst of the invention is used for C5 / C6 isomerization reaction and has high isomerization activity and low cracking activity.
[0004] CN110385142A discloses a catalyst for isobutane normalization reaction, which uses MCM-41 molecular sieve as a carrier and Pt / SO4 2- / ZrO2 is the active component. Although the reaction conditions are relatively mild, the isobutane conversion effect is not ideal. Under the condition that the n-butane selectivity is higher than 90%, the isobutane conversion rate does not exceed 21%, and the n-butane yield is lower than 22.1%.
[0005] The sulfated zirconium oxide type solid superacid catalyst disclosed in the prior art is usually used for isomerization or normalization of light hydrocarbons, and there is no report on its application in both reactions. In addition, when the catalyst disclosed in the prior art is used for isomerization or normalization reaction, it is difficult to balance the reaction conversion rate and target product selectivity, and the stability is insufficient. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems of insufficient activity and poor stability of the normal isomerization catalyst in the prior art, and to provide a normal isomerization catalyst having high light hydrocarbon normal isomerization activity and good stability.
[0007] In order to achieve the above object, the present invention provides a normal isomerization catalyst on one hand, the catalyst comprising an active matrix, and an active metal component supported on the active matrix;
[0008] Wherein, the active matrix includes the acidic active component SO4 2- / ZrO2, an all-silicon molecular sieve having an MFI structure, and alumina; the active metal component is selected from at least one of the noble metal elements;
[0009] Wherein, in the catalyst, the density of the strong acid center is 0.1-1 μmol / m 2 .
[0010] Preferably, in the catalyst, the molar ratio of the strong acid to the weak acid is 4-8:1.
[0011] The second aspect of the present invention provides a method for preparing the above-mentioned normal isomerization catalyst, the preparation method comprising:
[0012] (1) mixing an all-silicon molecular sieve having an MFI structure and zirconium hydroxide to obtain a mixture;
[0013] (2) contacting the mixture with a solution containing sulfate;
[0014] (3) mixing the product obtained in step (2), an alumina precursor and an optional peptizing agent, forming and calcining the mixture to obtain an active matrix;
[0015] (4) The active metal component is loaded on the active matrix.
[0016] The third aspect of the present invention provides the use of the normal isomerization catalyst described in the first aspect or the normal isomerization catalyst prepared by the preparation method described in the second aspect in the isomerization reaction or normalization reaction of C4-C6 light hydrocarbons.
[0017] The catalyst provided by the present invention comprises an active matrix and an active metal component, and the active component SO4 2- / ZrO2 and active metal components provide strong acid and weak acid respectively, and further adjust the density of the strong acid center of the catalyst through the synergistic effect of all-silicon molecular sieve with MFI structure and alumina. The catalyst has a suitable density of strong acid centers, and has high isomerization activity and normalization activity. It can be used in the isomerization reaction or normalization reaction of C4-C6 light hydrocarbons, and can have both high conversion rate and selectivity, and good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is the XRD spectra of the all-silicon MFI molecular sieve, white carbon black, MCM-41 molecular sieve and ZSM-5 molecular sieve used in the examples and comparative examples of the present invention;
[0019] Figure 2 It is the XRD spectra of the active matrix prepared in Examples 1-3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0020] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0021] The first aspect of the present invention provides a normal isomerization catalyst, the catalyst comprising an active matrix, and an active metal component supported on the active matrix;
[0022] Wherein, the active matrix includes the acidic active component SO4 2- / ZrO2, an all-silicon molecular sieve having an MFI structure, and alumina; the active metal component is selected from at least one of the noble metal elements;
[0023] Wherein, in the catalyst, the density of the strong acid center is 0.1-1 μmol / m 2 .
[0024] The phase analysis of the catalyst samples was carried out using a Japanese Rigaku D / MAX-3A diffractometer (XRD) under the following analysis conditions: radiation source CuKα target, Ni filter, scanning range 5°-70°, step width 0.02°.
[0025] In the solid acid catalyst system in the prior art, molecular sieves are usually used as carriers, and the molecular sieves used as carriers occupy a relatively high content in the catalyst; at the same time, the silicon-aluminum molecular sieve introduced into the catalyst is also usually used to provide additional acidic active centers.
[0026] The catalyst provided by the present invention has a suitable density of strong acid centers, while the density of strong acid centers in the super strong solid acid sulfate zirconium oxide in the prior art is relatively high, generally higher than 2 μmol / m 2 The inventors of the present invention have found in their research that a high density of strong acid centers may be detrimental to the normal isomerization selectivity of the catalyst.
[0027] According to the present invention, a small amount of all-silicon molecular sieve and alumina with an MFI structure can play a role in adjusting the distribution of strong acid centers of the solid acid catalyst, so that the catalyst has higher positive isomerization activity and selectivity. Furthermore, the noble metal component and the sulfated zirconium oxide in the active matrix act synergistically, and the stability of the catalyst can be improved through the joint action of the strong acid center and the weak acid center. The reason is that the all-silicon molecular sieve with an MFI structure has a special pore structure, is basically non-acidic, and has excellent thermal stability, which helps to optimize the distribution of strong acid centers in the sulfated zirconium oxide, facilitates the efficient activation and conversion of light hydrocarbon molecules through a single molecule path, and facilitates the diffusion of reactants and products, thereby effectively avoiding the occurrence of secondary reactions.
[0028] According to some preferred embodiments of the present invention, the density of the strong acid center in the catalyst is 0.2-0.7 μmol / m 2 For example, it can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7 μmol / m 2 In the above preferred case, it is beneficial to further improve the activity and selectivity of the catalyst in the normal isomerization reaction of light hydrocarbons.
[0029] In the present invention, the density of the strong acid center is the ratio of the amount of strong acid in the catalyst to the specific surface area. The method for testing the amount of acid in the catalyst includes: using a Nicolet 6700 Fourier transform infrared spectrometer produced by Thermo Fisher, USA, with a resolution of 4 cm -1 , scanned 64 times. The sample was pressed into a self-supporting sheet with a diameter of 13 mm, and then placed in a muffle furnace for high-temperature calcination. After completion, it was directly transferred to a dryer for cooling at high temperature. After cooling to room temperature, it was placed in a homemade quartz infrared sample cell, first treated at 400°C for 2 hours under normal pressure flowing air, then cooled to 200°C, vacuum purified for 4 hours, and then cooled to -190°C with liquid nitrogen. The purified CO probe molecules were saturated and adsorbed for 0.5 hours before desorption. The spectra before and after adsorption were subtracted to obtain the infrared spectrum of the sample adsorbed CO. For the wave number of 2050-2250cm -1 The spectrum at 2186cm is processed by peak separation. The spectrum can be divided into four absorption peaks with wave numbers of 2186cm -1 、2167cm -1 、2150cm -1 and 2125cm -1 , where the wave number is 2167cm -1 The absorption peak at 2150 cm is a strong acid center directly related to the catalyst performance. -1 The absorption peak at is the weak acid center of the catalyst. The acid amount N (in μmol / g) is calculated according to formula (1).
[0030] N=A / (ρA0), formula (1),
[0031] Where A is the integrated area of the absorption peak (in cm -1 ), ρ is the mass of the catalyst support per square centimeter (in g / cm 2 ), A0 is the molar extinction coefficient, for a wave number of 2167 cm -1 and 2150cm -1 The spectral peak is A0=2.6cm / μmol.
[0032] In the present invention, the catalyst specific surface area is characterized by low temperature nitrogen static volume adsorption method (BET method), the instrument used is ASAP2400 specific surface measuring instrument produced by Micromeritics Instrument Company, the pretreatment conditions are: 250 ° C, 1.3 Pa, treatment for 4 hours, and the specific surface area (m 2 / g).
[0033] According to some preferred embodiments of the present invention, in the catalyst, the molar ratio of the strong acid to the weak acid is 4-8:1, for example, it can be 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1 and other typical but non-limiting molar ratios. Preferably, it is 4.5-6.8:1. In the above preferred case, it is conducive to further improving the stability of the catalyst.
[0034] According to some preferred embodiments of the present invention, based on the total mass of the catalyst, the content of the active matrix is 99-99.95wt%, preferably 99.5-99.9wt%; calculated as an element, the content of the active metal component is 0.05-1wt%, preferably 0.1-0.5wt%.
[0035] In the present invention, the content of active metal components in the catalyst is determined by Lambda 35 UV-Vis spectrophotometer or ICP-AES. When the catalyst contains only active matrix and active metal components, the sum of the content of active matrix and active metal components is 100%.
[0036] According to some preferred embodiments of the present invention, the active metal component is selected from at least one of Pt, Pd, Ru and Rh, preferably Pt and / or Pd.
[0037] In the present invention, the active metal component exists in the form of oxide and / or metal. Preferably, at least part of the active metal component exists in the form of metal.
[0038] According to some preferred embodiments of the present invention, the active matrix includes zirconium, silicon, aluminum and sulfur, and the content of zirconium oxide, silicon oxide, aluminum oxide and SO3 is 30-90wt% based on the total mass of the active matrix, 1-35wt% based on the total mass of the active matrix, 5-50wt% based on the total mass of the active matrix, 50-80wt% based on the total mass of the active matrix, 5-30wt% based on the total mass of the active matrix, 5-30wt% based on the total mass of the active matrix, 5-30wt% based on the total mass of the active matrix, 2-8wt% based on the total mass of the active matrix. Under the above preferred composition, it is beneficial to improve the thermal stability of tetragonal zirconium oxide and the specific surface area of the catalyst, so that the catalyst has a suitable distribution of strong acid centers and accessibility of active centers, and further improves the catalytic activity of the catalyst.
[0039] According to some preferred embodiments of the present invention, the mass ratio of SO3 to ZrO2 is (0.02-0.12):1, preferably (0.03-0.08):1.
[0040] In the present invention, the composition of the active matrix is characterized and analyzed using an XRF-1800 wavelength dispersive X-ray fluorescence spectrometer, and the content of each element in the sample is obtained through theoretical calculation and mathematical correction based on the intensity of the elements present in the sample obtained by scanning and the pure substance sensitivity of these elements in the instrument.
[0041] According to some preferred embodiments of the present invention, in the active matrix, the mass ratio of the acidic active component calculated as ZrO2 to the mass ratio of the all-silicon molecular sieve calculated as SiO2 is 1:(0.1-1), preferably 1:(0.15-0.5).
[0042] In the present invention, there is no particular limitation on the shape of the catalyst, and those skilled in the art can select it according to actual needs. For example, it can be in the form of strips, pellets, sheets, particles or microspheres, suitable for fixed bed, moving bed or fluidized bed reactions.
[0043] The second aspect of the present invention provides a method for preparing the above-mentioned normal isomerization catalyst, the preparation method comprising:
[0044] (1) mixing an all-silicon molecular sieve having an MFI structure and zirconium hydroxide to obtain a mixture;
[0045] (2) contacting the mixture with a solution containing sulfate;
[0046] (3) mixing the product obtained in step (2), an alumina precursor and an optional peptizing agent, forming and calcining the mixture to obtain an active matrix;
[0047] (4) The active metal component is loaded on the active matrix.
[0048] According to the present invention, the above-mentioned preparation method can make the all-silicon molecular sieve with MFI structure evenly distributed in the catalyst without blocking the catalyst pores, and the density of the strong acid center in the sulfated zirconium oxide is reduced without introducing new acid centers, and the existence of strong acid sites with suitable density and uniform strength has higher normal isomerization activity and selectivity.
[0049] The present invention has a wide selection range for the number of pores and the pore structure of the all-silicon molecular sieve, and any all-silicon molecular sieve with an MFI structure can be applied to the present invention.
[0050] In some preferred embodiments, the specific surface area of the all-silicon molecular sieve is 400-500m 2 / g, preferably 420-460m 2 In the above preferred case, it is beneficial to further optimize the density of the strong acid center in the sulfated zirconium oxide, improve the uniformity of the strong acid site in the catalyst, and thus improve the normal isomerization activity.
[0051] According to some preferred embodiments of the present invention, the mass ratio of the zirconium hydroxide calculated by the mass of ZrO2 to the all-silicon molecular sieve calculated by the mass of SiO2 is 1:(0.15-0.5).
[0052] In the present invention, the acidic active component is formed by contacting the mixture with a solution containing sulfate in step (2). The contact can be carried out in a conventional manner in the art, for example, the mixture can be impregnated with a solution containing sulfate.
[0053] The present invention has no particular limitation on the specific operating conditions of the contact, as long as the catalyst composition range described above is met, and those skilled in the art can make the selection according to actual needs.
[0054] According to some preferred embodiments of the present invention, the contacting temperature is 20-80°C, preferably 25-60°C; and the contacting time is 1-10h, preferably 2-5h.
[0055] The present invention has a wide range of selection for the specific type of the solution containing sulfate radicals. Preferably, the solution containing sulfate radicals is selected from an aqueous solution of at least one of sulfuric acid, ammonium sulfate and ammonium bisulfate.
[0056] Preferably, the concentration of sulfate in the solution containing sulfate is 1-10wt%, preferably 2-8wt%. The above preferred embodiment is conducive to obtaining a suitable SO3 content and strong acid center density.
[0057] The present invention has no particular limitation on the amount of the solution containing sulfate, as long as it meets the requirements of the SO3 content range in the catalyst described in the first aspect, and those skilled in the art can select it according to actual needs. Preferably, the mass ratio of the solution containing sulfate to the mixture is 0.3-5:1, preferably 0.5-3:1.
[0058] In the present invention, after the contacting in step (2), an optional drying and grinding step is further included. The drying temperature may be 50-150° C., and the drying time may be 3-100 hours. The grinding is used to grind the dried solid into a powder of 100-300 meshes, which is beneficial to improve the crushing strength of the catalyst in the above preferred case.
[0059] In the present invention, the alumina precursor refers to a substance that can obtain alumina by calcination, which is well known to those skilled in the art. Preferably, the alumina precursor is pseudo-boehmite and / or gibbsite, preferably pseudo-boehmite. In the above preferred case, it is beneficial to improve the thermal stability and crushing strength of the catalyst.
[0060] In the present invention, the molding in step (3) can be carried out by conventional methods and conditions in the art, and the present invention has no particular limitation thereto. The molding method can be selected according to the actual application needs, for example, it can be selected from any one of extrusion molding, granulation molding, ball rolling molding and spray drying spheronization, preferably extrusion molding. In the above preferred case, it is more suitable for a fixed bed reactor.
[0061] According to some preferred embodiments of the present invention, the total mass ratio of the peptizing agent to the product obtained in step (2) to the alumina precursor is 0.3-1:1, preferably 0.4-0.8:1.
[0062] According to some preferred embodiments of the present invention, the peptizing agent is an aqueous solution of an acid, preferably an aqueous solution of at least one selected from nitric acid, acetic acid, citric acid, oxalic acid and formic acid.
[0063] Preferably, the concentration of the acid in the peptizing agent is 2-10 wt %.
[0064] According to some preferred embodiments of the present invention, in step (3), the calcination temperature is 600-850° C., preferably 650-850° C., and the calcination time is 1-20 hours, preferably 3-12 hours. Under the above preferred calcination temperature conditions, it is beneficial to form a strong acid center with a suitable density, which is beneficial to improve the activity and selectivity of the catalyst in the normal isomerization reaction of light hydrocarbons.
[0065] In the present invention, step (3) may further include a drying process before the calcination. Preferably, the drying temperature is 80-140° C., preferably 100-130° C., and the drying time is 5-30 hours, preferably 8-24 hours.
[0066] In the present invention, the active metal component can be loaded on the active matrix by any conventional method in the art. Preferably, the method of loading the active metal component on the active matrix comprises: impregnating the active matrix with a solution containing a soluble compound of the active metal, followed by drying and calcining.
[0067] The present invention has a wide selection range for the soluble compound of the active metal, which can be an inorganic salt or an organic salt of the active metal. When the active metal is Pt, the soluble compound of Pt is preferably at least one of chloroplatinic acid, platinum tetrachloride, ammonium chloroplatinate and dinitrosodiamine platinum. When the active metal is Pd, the soluble compound of Pd can be, for example, palladium chloride.
[0068] In the present invention, the solution containing the soluble compound of the active metal is a solution obtained by dissolving the soluble compound of the active metal in a solvent. The present invention has no particular limitation on the type of solvent, as long as it can dissolve the soluble compound of the active metal, for example, it can be water.
[0069] According to some preferred embodiments of the present invention, in order to make the soluble compound containing active metal more evenly loaded on the active matrix and further improve the stability of the catalyst, the solution also contains a competitive adsorbent. The competitive adsorbent is preferably at least one of sulfuric acid, nitric acid and acetic acid, more preferably nitric acid.
[0070] Preferably, the mass ratio of the competitive adsorbent to the soluble compound of the active metal is 1-20: 1, preferably 2-10: 1. The above preferred embodiment is conducive to the uniform dispersion of the soluble compound containing the active metal in the active matrix, while effectively preventing the competitive adsorbent from damaging the structure of the active matrix, further improving the activity stability of the catalyst.
[0071] The present invention has no particular limitation on the amount of the solution containing the soluble compound of the active metal, as long as the amount of the active metal component meets the range described in the first aspect. Preferably, the mass ratio of the amount of the solution containing the soluble compound of the active metal to the active matrix is 0.4-1:1, preferably 0.5-0.8:1.
[0072] According to the present invention, the impregnated product is dried and calcined. The present invention has no particular requirements for the specific conditions of the drying, and the drying conditions conventional in the art can be used. Preferably, the drying temperature is 80-140°C, preferably 100-130°C, and the drying time is 5-30h, preferably 8-24h.
[0073] According to the present invention, preferably, the calcination temperature is 450-650° C., preferably 480-600° C., and the calcination time is 1-10 h, preferably 3-5 h.
[0074] According to some preferred embodiments of the present invention, the preparation method further comprises: subjecting the product obtained in step (4) to a reduction treatment in the presence of hydrogen.
[0075] According to some preferred embodiments of the present invention, the reduction treatment conditions include: temperature of 200-300°C, preferably 220-260°C, time of 1-10h, preferably 3-5h; gas volume ratio of 300-1500, preferably 500-1200.
[0076] The third aspect of the present invention provides the use of the normal isomerization catalyst described in the first aspect or the normal isomerization catalyst prepared by the preparation method described in the second aspect in the isomerization reaction or normalization reaction of C4-C6 light hydrocarbons.
[0077] The present invention will be described in detail below through examples.
[0078] The bulk structure of the catalysts in the following examples was analyzed and detected using a Rigaku D / MAX-3A diffractometer (XRD) of Japan. The analysis conditions were: radiation source CuKα target, Ni filter, scanning range 5°-70°, step width 0.02°.
[0079] The Pt content of the catalyst was determined using a Lambda 35 UV-Vis spectrophotometer. The sample was first dissolved in hydrochloric acid and then complexed with stannous chloride. The Pt content was determined by colorimetry.
[0080] ICP-AES was used to determine the Pd content of the catalyst. The sample was first nitrolyzed with aqua regia, then diluted and fixed to volume, and determined by atomic absorption spectrometry and compared with the standard curve to determine the Pd content.
[0081] The composition of the active matrix was characterized and analyzed using an XRF-1800 wavelength dispersive X-ray fluorescence spectrometer. Based on the intensity of the elements present in the scanned samples and the sensitivity of the instrument to the pure substances of these elements, the content of each element in the sample was obtained through theoretical calculation and mathematical correction.
[0082] The zirconium hydroxide powder used was purchased from Changling Catalyst Company, and the zirconium oxide content was 78.5% by weight.
[0083] The all-silicon MFI molecular sieve Si-1 used was purchased from Changling Catalyst Company, with a silicon oxide content of 99.7% by mass and a specific surface area of 444.6 m 2 / g, XRD characterization Figure 1 shown.
[0084] Pseudo-boehmite powder was purchased from Sasol, Germany, with an alumina content of 75% by mass.
[0085] Example 1
[0086] (1) Take 38.2g of zirconium hydroxide powder and 4.4g of all-silicon MFI molecular sieve Si-1 and mix them evenly, add 48.0g of 5% by mass sulfuric acid aqueous solution, immerse at 40°C for 4h, and dry the impregnated solid at 60°C for 12h and 120°C for 12h. Grind the dried solid into fine powder, pass through a 100-300 mesh sieve, mix evenly with 10.6g of pseudo-boehmite powder, add 5.0% by mass nitric acid aqueous solution for peptization, the ratio of the total mass of nitric acid aqueous solution to the fine powder and alumina precursor is 0.6:1, mix evenly and extrude into strips, dry the wet strips at 120°C for 10h, and calcine at 680°C for 4h to obtain the active matrix SSiZA-1. The XRD characterization results of the active matrix SSiZA-1 are shown in Figure 2 ,Depend on Figure 2 The characteristic peaks of all-silicon MFI molecular sieve can be seen in the figure, and the composition is shown in Table 1.
[0087] (2) 10.0 g of active matrix SSiZA-1 was added to 5.0 g of aqueous solution containing 0.0266 g of chloroplatinic acid and 0.1 g of nitric acid, and impregnated at 25°C for 3 h. The impregnated solid was dried at 120°C for 10 h and calcined at 550°C for 4 h to obtain catalyst CAT-1. The composition and physicochemical properties of the catalyst are shown in Table 2.
[0088] Example 2
[0089] (1) Take 38.2g of zirconium hydroxide powder and 7.8g of all-silicon MFI molecular sieve, mix them evenly, add 48.0g of 5% by mass sulfuric acid aqueous solution, soak at 40°C for 4h, and dry the impregnated solid at 60°C for 12h and 120°C for 12h. Grind the dried solid into fine powder, pass through a 100-300 mesh sieve, mix evenly with 10.6g of pseudo-boehmite powder, add 5.0% by mass nitric acid aqueous solution for peptization, the ratio of the total mass of nitric acid aqueous solution to the fine powder and alumina precursor is 0.5:1, knead evenly and extrude into strips, dry the wet strips at 120°C for 10h, and calcine at 680°C for 4h to obtain the active matrix SSiZA-2. The XRD characterization results of the active matrix SSiZA-2 are shown in Figure 2 , the composition is shown in Table 1.
[0090] (2) 10.0 g of the active matrix SSiZA-2 was added to 5.0 g of an aqueous solution containing 0.0266 g of chloroplatinic acid and 0.1 g of nitric acid, and the mixture was immersed at 25° C. for 3 h. The immersed solid was dried at 120° C. for 10 h and calcined at 550° C. for 4 h to obtain catalyst CAT-2. The composition and physicochemical properties of the catalyst are shown in Table 2.
[0091] Example 3
[0092] (1) Take 38.2g of zirconium hydroxide powder and 14.3g of all-silicon MFI molecular sieve Si-1 and mix them evenly, add 48.0g of 5% by mass sulfuric acid aqueous solution, immerse at 40°C for 4h, and dry the impregnated solid at 60°C for 12h and 120°C for 12h. Grind the dried solid into fine powder, pass through a 100-300 mesh sieve, mix evenly with 3.4g of pseudo-boehmite powder, add 5.0% by mass nitric acid aqueous solution for peptization, the ratio of the total mass of nitric acid aqueous solution to the fine powder and alumina precursor is 0.7:1, mix evenly and extrude into strips, dry the wet strips at 120°C for 10h, and calcine at 680°C for 4h to obtain the active matrix SSiZA-3. The XRD characterization results of the active matrix SSiZA-3 are shown in Figure 2 ,Depend on Figure 2 The characteristic peaks of all-silicon MFI molecular sieve can be seen in the figure, and the composition is shown in Table 1.
[0093] (2) 10.0 g of active matrix SSiZA-1 was added to 5.0 g of aqueous solution containing 0.0266 g of chloroplatinic acid and 0.1 g of nitric acid, and impregnated at 25°C for 3 h. The impregnated solid was dried at 120°C for 10 h and calcined at 550°C for 4 h to obtain catalyst CAT-3. The composition and physicochemical properties of the catalyst are shown in Table 2.
[0094] Example 4
[0095] The method of Example 1 was followed, except that 10 g of the active matrix SSiZA-1 was added to 5.0 g of an aqueous solution containing 0.0416 g of palladium chloride and 0.1 g of nitric acid, and the mixture was immersed at 25°C for 3 h. The immersed solid was dried at 120°C for 10 h and calcined at 550°C for 4 h to obtain catalyst CAT-4. The composition and physicochemical properties of the catalyst are shown in Table 2.
[0096] Example 5
[0097] (1) 38.2 g of zirconium hydroxide powder was added with 48.0 g of a 5% by mass sulfuric acid aqueous solution, and the mixture was immersed at 40° C. for 4 h. The immersed solid was dried at 60° C. for 12 h and at 120° C. for 12 h.
[0098] The dried solid was ground into fine powder, passed through a 100-300 mesh sieve, 4.4 g of all-silicon MFI molecular sieve and 10.6 g of pseudo-boehmite powder were added thereto, mixed evenly, and a 5.0 mass % nitric acid aqueous solution was added for peptization, the ratio of the total mass of the nitric acid aqueous solution to the fine powder, the MFI molecular sieve and the alumina precursor was 0.6:1, and after kneading evenly, the mixture was extruded into strips, and the wet strips were dried at 120°C for 10 h and calcined at 680°C for 4 h to obtain the active matrix SSiZA-4, the composition of which is shown in Table 1.
[0099] (2) 10.0 g of active matrix SSiZA-4 was added to 5.0 g of aqueous solution containing 0.0266 g of chloroplatinic acid and 0.1 g of nitric acid, and impregnated at 25°C for 3 h. The impregnated solid was dried at 120°C for 10 h and calcined at 550°C for 4 h to obtain catalyst CAT-5. The composition and physicochemical properties of the catalyst are shown in Table 2.
[0100] Example 6
[0101] The method of Example 2 is followed, except that the amount of chloroplatinic acid used in step (2) is 0.0106 g.
[0102] Catalyst CAT-6 was obtained. The composition and physicochemical properties of the catalyst are shown in Table 2.
[0103] Example 7
[0104] The method of Example 2 is followed, except that nitric acid is not introduced into the impregnation solution in step (2) as a competitive adsorbent.
[0105] Catalyst CAT-7 was obtained. The composition and physicochemical properties of the catalyst are shown in Table 2.
[0106] Comparative Example 1
[0107] (1) Take 38.2g of zirconium hydroxide powder, add 48.0g of 5% by mass sulfuric acid aqueous solution, immerse at 40°C for 4h, and dry the impregnated solid at 60°C for 12h and 120°C for 12h. Grind the dried solid into fine powder, pass through a 100-300 mesh sieve, mix evenly with 16.6g of pseudo-boehmite powder, add 5.0% by mass nitric acid aqueous solution for peptization, the ratio of the nitric acid aqueous solution to the total mass of the fine powder and the alumina precursor being 0.6:1, knead evenly and extrude into strips, dry the wet strips at 120°C for 10h, and calcine at 680°C for 4h to obtain the active matrix DSSiZA-1. The XRD characterization results of the active matrix DSSiZA-1 are shown in Figure 2 It can be seen that the catalyst DA1 does not contain the characteristic peak of all-silicon MFI molecular sieve Si-1. The composition is shown in Table 1.
[0108] (2) 10.0 g of the above-mentioned active matrix DSSiZA-1 was added to 5.0 g of an aqueous solution containing 0.0266 g of chloroplatinic acid and 0.1 g of nitric acid, and the mixture was immersed at 25° C. for 3 h. The immersed solid was dried at 120° C. for 10 h and calcined at 550° C. for 4 h to obtain the catalyst DCAT-1. The composition and physicochemical properties of the catalyst are shown in Table 2.
[0109] Comparative Example 2
[0110] (1) Take 38.2g zirconium hydroxide powder and 10.2g all-silicon MFI molecular sieve, mix them evenly, add 48.0g sulfuric acid aqueous solution with a concentration of 5% by mass, and immerse them at 40°C for 4h. The impregnated solid is dried at 60°C for 12h and 120°C for 12h. The dried solid is ground into fine powder, passed through a 100-300 mesh sieve, and peptized with nitric acid aqueous solution with a concentration of 5.0% by mass. The mass ratio of nitric acid aqueous solution to the fine powder is 0.6:1. After kneading evenly, the wet strips are extruded into strips. The wet strips are dried at 120°C for 10h and calcined at 680°C for 4h to obtain the active matrix DSSiZA-2. The composition of the active matrix DSSiZA-2 is shown in Table 1.
[0111] (2) 10.0 g of the active matrix DSSiZA-2 was added to 5.0 g of an aqueous solution containing 0.0266 g of chloroplatinic acid and 0.1 g of nitric acid, and the mixture was immersed at 25° C. for 3 h. The immersed solid was dried at 120° C. for 10 h and calcined at 550° C. for 4 h to obtain the catalyst DCAT-2. The composition and physicochemical properties of the catalyst are shown in Table 2.
[0112] Comparative Example 3
[0113] The method of Example 2 was followed, except that an equal mass of white carbon black Si-2 (produced by Changling Catalyst Company, with a silicon oxide content of 99.9% by mass, XRD characterization see Figure 1 ) was used to replace the all-silicon MFI molecular sieve Si-1. The active matrix DSSiZA-3 was prepared. The composition of the active matrix DSSiZA-3 is shown in Table 1.
[0114] Catalyst DCAT-3 was obtained. The composition and physicochemical properties of the catalyst are shown in Table 2.
[0115] Comparative Example 4
[0116] The method of Example 2 was followed, except that an equal mass of MCM-41 molecular sieve (denoted as Si-3, produced by Changling Catalyst Company, with a silicon oxide content of 99.7% by mass, XRD characterization see Figure 1 ) replaced the all-silicon MFI molecular sieve. The active matrix DSSiZA-4 was prepared. The composition of the active matrix DSSiZA-4 is shown in Table 1. From the results in Table 1, it can be seen that due to the poor thermal stability of MCM-41, the structure collapsed during high-temperature calcination, resulting in the loss of SO3 in the catalyst.
[0117] Catalyst DCAT-4 was obtained. The composition and physicochemical properties of the catalyst are shown in Table 2.
[0118] Comparative Example 5
[0119] The method of Example 2 was followed, except that an equal mass of ZSM-5 molecular sieve (denoted as Si-4, produced by Changling Catalyst Company, with a silicon oxide / aluminum oxide molar ratio of 65, XRD characterization see Figure 1 ) replaces the all-silica MFI molecular sieve.
[0120] The obtained active matrix is recorded as DSSiZA-5. The composition of the active matrix DSSiZA-5 is shown in Table 1.
[0121] Catalyst DCAT-5 was obtained. The composition and physicochemical properties of the catalyst are shown in Table 2.
[0122] Table 1
[0123]
[0124] Table 2
[0125]
[0126]
[0127] Test Example 1
[0128] The following test examples are used to examine the isomerization reaction performance of the catalyst.
[0129] Using n-butane with a purity of >99.8 mass % as the reaction raw material, the catalysts prepared in the above embodiments and comparative examples were first reduced with hydrogen in a small fixed bed reactor, and then the activity was evaluated. The hydrogen reduction conditions were: 260° C., gauge pressure 0.1 MPa, gas-to-agent volume ratio 800, and reduction for 3 h.
[0130] Evaluation conditions: 250°C, 1.8 MPa, feed mass space velocity 1.5 hr -1 , the hydrogen / hydrocarbon molar ratio was 1.5, and the evaluation results were recorded after 10h and 100h of reaction and are listed in Table 3.
[0131] n-Butane conversion rate (%) = ((mass of n-butane in the feedstock - mass of n-butane in the product) / mass of n-butane in the feedstock) × 100%;
[0132] Isobutane selectivity (%) = (mass of isobutane in the product / (mass of normal butane in the feedstock - mass of normal butane in the product)) x 100%.
[0133] Table 3
[0134]
[0135]
[0136] Test Example 2
[0137] The following test examples are used to investigate the normalization reaction stability of the catalyst.
[0138] Using isobutane with a purity of >99.8 mass % as the reaction raw material, the above catalyst and the comparative catalyst were first subjected to hydrogen reduction in a small fixed bed reactor, and then the activity was evaluated. The hydrogen reduction conditions were: 260° C., gauge pressure 0.1 MPa, gas-to-agent volume ratio 800, and reduction for 3 h.
[0139] Evaluation conditions: 260°C, 1.8 MPa, feed mass space velocity 2.0 hr -1 , the hydrogen / hydrocarbon molar ratio was 2.0, and the evaluation results were recorded after 10h and 100h of reaction and are listed in Table 4.
[0140] Wherein, isobutane conversion rate (%) = ((mass of isobutane in the feedstock - mass of isobutane in the product) / mass of isobutane in the feedstock) × 100%;
[0141] Normal butane selectivity (%) = (mass of normal butane in the product / (mass of isobutane in the feedstock - mass of isobutane in the product)) x 100%.
[0142] Table 4
[0143]
[0144]
[0145] It can be seen from the results of Table 3 and Table 4 that the catalyst prepared in the embodiment of the present invention has both high normal isomerization activity and selectivity. The all-silicon molecular sieve and alumina with MFI structure can play a role in adjusting the distribution of the strong acid center of the solid acid catalyst, so that the catalyst has excellent normal isomerization activity and good selectivity. At the same time, the selectivity retention rate of the normal isomerization of the catalyst after 100h reaction is above 99%, indicating that the catalyst has good activity stability.
[0146] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A normal isomerization catalyst, characterized in that The catalyst comprises an active matrix and an active metal component supported on the active matrix; Wherein, the active matrix includes the acidic active component SO4 2- / ZrO2, an all-silicon molecular sieve having an MFI structure, and alumina; the active metal component is selected from at least one of the noble metal elements; Wherein, in the catalyst, the density of the strong acid center is 0.1-1 μmol / m 2 .
2. The catalyst according to claim 1, wherein In the catalyst, the density of the strong acid center is 0.2-0.7 μmol / m 2 ; Preferably, in the catalyst, the molar ratio of the strong acid to the weak acid is 4-8:
1.
3. The catalyst according to claim 1 or 2, wherein Based on the total mass of the catalyst, the content of the active matrix is 99-99.95wt%, preferably 99.5-99.9wt%; based on the element, the content of the active metal component is 0.05-1wt%, preferably 0.1-0.5wt%; Preferably, the active metal component is selected from Pt and / or Pd.
4. The catalyst according to any one of claims 1 to 3, wherein The active matrix includes zirconium, silicon, aluminum and sulfur, respectively calculated as zirconium oxide, silicon oxide, aluminum oxide and SO3, based on the total mass of the active matrix, the content of zirconium oxide is 30-90wt%, the content of silicon oxide is 1-35wt%, the content of aluminum oxide is 5-50wt%, and the content of SO3 is 1-10wt%; Preferably, based on the total mass of the active matrix, the content of zirconium oxide is 50-80wt%, the content of silicon oxide is 5-30wt%, the content of aluminum oxide is 5-30wt%, and the content of SO3 is 2-8wt%; Preferably, the mass ratio of SO3 to ZrO2 is (0.02-0.12):1, preferably (0.03-0.08):
1.
5. The catalyst according to any one of claims 1 to 4, wherein In the active matrix, the mass ratio of the acidic active component calculated as ZrO2 to the mass ratio of the all-silicon molecular sieve calculated as SiO2 is 1:(0.1-1), preferably 1:(0.15-0.5).
6. A method for preparing the n-isomerization catalyst according to any one of claims 1 to 5, comprising: (1) mixing an all-silicon molecular sieve having an MFI structure and zirconium hydroxide to obtain a mixture; (2) contacting the mixture with a solution containing sulfate; (3) mixing the product obtained in step (2), an alumina precursor and an optional peptizing agent, forming and calcining the mixture to obtain an active matrix; (4) The active metal component is loaded on the active matrix.
7. The preparation method according to claim 6, wherein: The specific surface area of the all-silicon molecular sieve is 400-500m 2 / g; Preferably, the mass ratio of the zirconium hydroxide calculated by the mass of ZrO2 to the all-silicon molecular sieve calculated by the mass of SiO2 is 1:(0.15-0.5).
8. The preparation method according to claim 6 or 7, wherein: The contact temperature is 20-80°C, preferably 25-60°C; the contact time is 1-10h, preferably 2-5h; Preferably, the solution containing sulfate radicals is selected from an aqueous solution of at least one of sulfuric acid, ammonium sulfate and ammonium bisulfate; Preferably, the concentration of sulfate in the solution containing sulfate is 1-10wt%, preferably 2-8wt%; Preferably, the mass ratio of the solution containing sulfate to the mixture is 0.3-5:1, preferably 0.5-3:
1.
9. The preparation method according to any one of claims 6 to 8, wherein: The alumina precursor is pseudo-boehmite and / or gibbsite, preferably pseudo-boehmite; Preferably, the total mass ratio of the peptizing agent to the product obtained in step (2) to the alumina precursor is 0.3-1:1; Preferably, the peptizing agent is an aqueous solution of an acid, preferably an aqueous solution of at least one selected from nitric acid, acetic acid, citric acid, oxalic acid and formic acid.
10. The preparation method according to any one of claims 6 to 9, wherein: The molding method is selected from any one of extrusion molding, granulation molding, ball rolling molding and spray drying into balls, preferably extrusion molding; Preferably, in step (3), the calcination temperature is 600-850°C, preferably 650-850°C, and the calcination time is 1-20h, preferably 3-12h.
11. The preparation method according to any one of claims 6 to 10, wherein: The method of loading the active metal component on the active matrix comprises: impregnating the active matrix with a solution containing a soluble compound of the active metal, followed by drying and calcining; Preferably, the solution further contains a competitive adsorbent, and the competitive adsorbent is preferably at least one of sulfuric acid, nitric acid and acetic acid; Preferably, the mass ratio of the competitive adsorbent to the soluble compound of the active metal is 1-20:
1.
12. The preparation method according to any one of claims 6 to 11, wherein: The preparation method further comprises: subjecting the product obtained in step (4) to reduction treatment in the presence of hydrogen; Preferably, the reduction treatment conditions include: temperature of 200-300° C., preferably 220-260° C., time of 1-10 h, preferably 3-5 h; gas volume ratio of 300-1500, preferably 500-1200.
13. Use of the n-isomerization catalyst described in any one of claims 1 to 5 or the n-isomerization catalyst prepared by the preparation method described in any one of claims 6 to 12 in isomerization reaction or normalization reaction of C4-C6 light hydrocarbons.
Citation Information
Patent Citations
Super-strong acid mesoporous material synthesized in one pot and preparing method
CN101024187A
Solid superacid catalyst for n-heptane isomerization reaction and preparation method thereof
CN103611552A
Preparation method of zirconium-containing solid super acid
CN104971770A
Catalyst for isobutane normal reaction and preparation method and application of catalyst
CN110385142A
Solid acid catalysis and separation integrated filler as well as preparation method and application thereof
CN114100644A